Photocatalytical Properties and Theoretical Analysis of N, Cd-Codoped TiO2 Synthesized by Thermal Decomposition Method - Hongtao Gao; Bing Lu; Fangfang Liu; Yuanyuan Liu; Xian Zhao (International Journal of Photoenergy)
N, Cd-codoped TiO2 have been synthesized by thermal decomposition method. The products were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), UV-visible diffuse reflectance spectra (DRS), X-ray photoelectron spectroscopy (XPS), and Brunauer-Emmett-Teller (BET) specific surface area analysis, respectively. The products represented good performance in photocatalytic degradation of methyl orange. The effect of the incorporation of N and Cd on electronic structure and optical properties of TiO2 was studied by first-principle calculations on the basis of density functional theory (DFT). The impurity states, introduced by N 2p or Cd 5d, lied between the valence band and the conduction band. Due to dopants, the band gap of N, Cd-codoped TiO2 became narrow. The electronic transition from the valence band to conduction band became easy, which could account for the observed photocatalytic performance of N, Cd-codoped TiO2. The theoretical analysis might provide a probable reference for the experimentally element-doped TiO2 synthesis.